2014
DOI: 10.1007/978-3-642-54215-2_23
|View full text |Cite
|
Sign up to set email alerts
|

Trpa1

Abstract: The transient receptor potential ankyrin subtype 1 protein (TRPA1) is a nonselective cation channel permeable to Ca(2+), Na(+), and K(+). TRPA1 is a promiscuous chemical nocisensor that is also involved in noxious cold and mechanical sensation. It is present in a subpopulation of Aδ- and C-fiber nociceptive sensory neurons as well as in other sensory cells including epithelial cells. In primary sensory neurons, Ca(2+) and Na(+) flowing through TRPA1 into the cell cause membrane depolarization, action potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
201
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(212 citation statements)
references
References 297 publications
7
201
0
2
Order By: Relevance
“…However, it is not likely that species differences in the TRPA1 sequence are responsible for this discrepancy. TRPA1 is highly conserved between rats and mice (97% identity), and the residues previously proposed to be important for channel activation are identical (6). Previous reports of thermal and mechanical hyperalgesia, which develop both in hyperglycemic and normoglycemic STZ-treated rats, therefore support our behavioral findings (43,44).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, it is not likely that species differences in the TRPA1 sequence are responsible for this discrepancy. TRPA1 is highly conserved between rats and mice (97% identity), and the residues previously proposed to be important for channel activation are identical (6). Previous reports of thermal and mechanical hyperalgesia, which develop both in hyperglycemic and normoglycemic STZ-treated rats, therefore support our behavioral findings (43,44).…”
Section: Discussionsupporting
confidence: 89%
“…The major current treatments target the management of pain with anti-convulsant, anti-depressant, and opioid drugs that often have limited efficacy or unacceptable side effects (4). The ion channel TRPA1 is expressed in a subset of nociceptive sensory neurons where it acts as a promiscuous receptor for oxidants and electrophilic agents, but it is also activated by a number of nonreactive compounds (6). Covalent modification of cysteine residues present in the intracellular N terminus of TRPA1 is thought to underlie the agonist activity of oxidants and electrophilic agonists (7,8).…”
Section: Streptozotocin (Stz)-induced Diabetes Is the Most Commonly Umentioning
confidence: 99%
“…Importantly, the authors concluded that this could best be explained by an effect on the coupling of temperature to channel gating rather than altering the nature of the thermosensitive domain itself (30). This reasoning is in line with our view that conformational changes of the N-terminal ARD indirectly affect thermo-and chemosensitive structures outside the N-terminal ARD of TRPA1 (10,14). Studies of purified TRPA1 without its N-terminal ARD should therefore be a valuable contribution in the search for TRPA1 thermo-and chemosensory domains (14).…”
supporting
confidence: 71%
“…A role for mammalian TRPA1, and especially the human TRPA1 (hTRPA1), as noxious cold sensors has been controversial ever since it was proposed (13), whereas the heat-sensitive role of TRPA1 homologues in non-mammalians has been easily accepted (5,10). However, we have recently shown that hTRPA1 is indeed an intrinsically cold-sensitive protein (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation